The childbirth experiences of adolescent mothers in the Western Cape - Füzy, Elizabeth (Division of Nursing and Midwifery, 2016)
Objective: The objective of this study was to explore the lived childbirth experiences of middle adolescent mothers between 14 and 16 years of age. Methodology: A qualitative design was followed, using Husserl's phenomenological approach. Information was gathered by semi-structured conversations. Identified themes and sub-themes (Colaizzi's steps) were presented to participants for authentication during follow-up conversations. Study Setting: Two hospitals in the Cape Town Metropolitan area, Western Cape, South Africa. Participants: Six adolescent girls between the ages of 14 and 16 years of age who had normal vaginal births of healthy, term infants. Findings: An over-arching theme of preservation of personhood was identified. Themes and sub-themes were derived according to three Husserlian phenomenological concepts. Within these concepts three essential themes emerged from the conversations: i) essences: physically underdeveloped and emotionally unprepared for childbirth, ii) intentionality and consciousness: an unsettled state of mind during childbirth, and iii) life-world: feeling physically and emotionally overwhelmed by the experience. Conclusion: The participants highly valued the presence of a support person; they indicated that their mothers were their first choice. Friendly, helpful, respectful and non-judgmental care from nurses and midwives were associated with more positive birth experiences while humiliation, victimisation and rudeness were associated with negative birth experiences. Implications for adolescent-friendly practice: A condensed form of antenatal education is needed together with adolescent-friendly health care services to ensure better preparedness and experiences. Shared-decision making regarding certain aspects of childbirth is necessary. Continuous labour support is an important coping strategy and pain management is vital. Additional training is needed to address midwives' attitudes. Quality assessment tools are needed to address the mistreatment of maternity patients in health care facilities.